Key Drivers of Cloud Accounting Utilization by Small and Medium Enterprises in Zimbabwe - Dlamini, Banele (International Journal of Economics and Financial Issues, 2025)
This paper investigated the factors influencing the utilisation of cloud accounting among Small and Medium Enterprises (SMEs) in Zimbabwe. The study adopted a mixed-research approach. The study used stratified simple random sampling techniques, stratifying according to firm size. Data was collected using 141 questionnaires and 10 semi-structured interviews. Quantitative data was analysed using SPSS version 22.0, and qualitative data was thematically analysed using content analysis. The study found that the adoption and utilization of cloud accounting among SMEs in Zimbabwe are significantly influenced by lack of knowledge on cloud accounting, top management support, security concerns, data privacy, organizational readiness, availability of resources, legal compliance, government support, and vendor support. The study recommends that SMEs should allocate resources to upgrade necessary IT infrastructure, including reliable internet access and secure hardware, to support cloud accounting systems. The Zimbabwean government should offer grants, subsidies, or tax incentives to encourage SMEs to adopt cloud accounting and financial support can help mitigate initial investment costs. Moreover, the government as the major stakeholder should conduct workshops, seminars, and training programs to educate SMEs about the benefits and functionalities of cloud accounting.